An overview of the construction techniques of traditional Malay houses: Rumah Kutai, Perak - Khairuddin, Khairul Fikri; Salleh, Nurul Hamiruddin; Aripin, Srazali (2018)
Rumah Kutai in Perak is amongst the oldest surviving traditional Malay house and is gradually disappearing from the indigenous cultural landscape of Malaysia. Therefore, it is crucial to preserve such precious Malay heritage especially on the unique construction methods for the next generation references. The subject of the research is construction techniques of the traditional Malay houses which is emphasized on the indigenous house of Perak, Rumah Kutai. This research, basically exploring on how Rumah Kutai is being constructed from the beginning until the end. Also, to examine the construction techniques especially on the jointing system (tanggam) of several components in Rumah Kutai. The research aims to study the construction techniques of traditional Rumah Kutai.